A Focused Review on Cognitive Improvement by the Genus Salvia L. (Sage)-From Ethnopharmacology to Clinical Evidence - Abdulselam Ertas; Serkan Yigitkan; Ilkay Erdogan Orhan (MDPI AG, 2023)
Ethnopharmacology has been an important starting point in medical and pharmaceutical sciences for discovering drug candidates from natural sources. In this regard, the genus Salvia L., commonly known as sage, is one of the best-known medicinal and aromatic plants of the Lamiaceae family; it has been recorded as being used for memory enhancement in European folk medicine. Despite the various uses of sage in folk medicines, the records that have pointed out sage's memory-enhancing properties have paved the way for the aforementioned effect to be proven on scientific grounds. There are many preclinical studies and excellent reviews referring to the favorable effect of different species of sage against the cognitive dysfunction that is related to Alzheimer's disease (AD). Hence, the current review discusses clinical studies that provide evidence for the effect of Salvia species on cognitive dysfunction. Clinical studies have shown that some Salvia species, i.e., hydroalcoholic extracts and essential oils of S. officinalis L. and S. lavandulaefolia leaves in particular, have been the most prominently effective species in patients with mild to moderate AD, and these species have shown positive effects on the memory of young and healthy people. However, the numbers of subjects in the studies were small, and standardized extracts were not used for the most part. Our review points out to the need for longer-term clinical studies with higher numbers of subjects being administered standardized sage preparations.